Application of a novel catalyst in the esterification of mixed industrial palm oil for biodiesel production - Hayyan, A.; Hashim, M.A.; Hayyan, M. (2015)
Mixed industrial palm oil (MIPO) is proposed in this study as a renewable and agro-industrial raw material to produce biodiesel fuel. MIPO was obtained by mixing of acidic crude palm oil with sludge palm oil. Due to the high level of free fatty acid (FFA) in MIPO (8.5 ), esterification is needed to remove the acidity to the minimum level before biodiesel production. This is the first time 1-propanesulphonic acid (1-PSA) has been introduced as a catalyst for the pretreatment of MIPO. Using optimum conditions, the FFA content was successfully reduced from 8.5 to less than 1 . The biodiesel produced meets the international standards (ASTM D6751 and EN 14214). 1-PSA is therefore a promising catalyst that can be used to treat various types of acidic oils.